The Contract-Programs in Universities: Lessons from the International Comparison - García de Fanelli, Ana M. (Education Policy Analysis Archives, 2006)
In 2005, the Ministry of Education of Argentina launched a new policy to allocate public funds to national universities: the contractualization policy. Its purpose is to allocate funds to improve teaching quality based on an institutional plan defined by each university. It is expected that this plan addresses the main weaknesses detected during the external assessment coordinated by the National Committee of University Assessment and Accrediting (CONEAU). This paper presents the main findings of a research project carried out to help in the design of this contractualization policy. The two most important antecedents, the French and the Catalonian cases, are examined through the study of official documents, on-site observation of the French negotiation processes, and interviews with government and university key officials. The study concludes with the main lessons learned from these experiences and shows that this mechanism has clear advantages when aligning the strategic objectives that the government and universities have, in order to improve university quality.